THE IMPLEMENTATION OF RUNNING DICTATION GAME TO CREATE ACTIVE AND PRODUCTIVE LEARNING - Muamar Taofik; Ikhsanudin Ikhsanudin; Urai Salam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractImplementation of Running Dictation Game to students was interesting because it could motivate students to show their ability in English language learning activities. Besides, Running Dictation Game gave a chance to students to express their ideas individually or in a group in the classroom. This technique could make students be creative, active and productive in learning activities. In addition, when the students were involved in this learning activity using this technique, they experienced fun, happy and enjoyable atmosphere in the classroom. This study aims to implement Running Dictation Game in learning activities. To collect the data, the researcher observed students’ activeness and students’ productivity in a lesson with Recount text as the topic. The data was analyzed using classroom action research. It was expected that students learn more actively and productively in Recount Text lesson.Keywords: Active Learning, Classroom Action Research, Productive Learning Running Dictation Game,